Conception et analyse d’antennes à résonateur diélectrique pour les applications sans fil - Radjaa NOUIBAT; ENC/ Mohamed SAHED (University of M'sila, 2024)
EN To stay up with the requirements of modern cellular systems, which are indicated by the need to support wide-range applications, the DRA antenna is considered one of the sectors that is witnessing exceptional progress and increasing interest at the present time. This is due to its characteristics that distinguish it from other antennas. In this work, we have improved some of the disadvantages of this antenna, which can operate at a frequency of 0.8 GHz through a slot in the ground. The final shape of the designed DRA antenna was achieved using an in-depth parametric study that allows us to get a good idea of the effect of each parameter on the antenna patch, such as buffer lengths. The optimization process was run using the PSO algorithm integrated into the CST software